Determinants of Islamic Religious Teachers’ Effectiveness in Moral Development of Public High School Students - Samsuriadi, Samsuriadi; Suardi, Suardi (Journal of Educational Sciences, 2025)
Moral development is a central goal of Islamic Religious Education (PAI) in Indonesian public high schools, yet PAI teachers face intersecting institutional, sociocultural, and pedagogical challenges. This study investigates key factors that support or hinder their efforts to foster students’ akhlak. Using a qualitative case study at State High School 13 Makassar, data were gathered through interviews, observations, and document analysis, then analyzed thematically within the framework of Islamic character education. The findings highlight enabling conditions such as well-equipped religious facilities, routine worship and Qur’an literacy, strong parental involvement, and consistent leadership and supervision. Conversely, digital and peer environmental pressures, uneven student readiness, and limited instructional time act as major barriers. These factors interact, with institutional support enhancing the effectiveness of reflective pedagogy and family–school collaboration, while external challenges demand systemic interventions. The study proposes a determinants-of-effectiveness framework that views moral formation as the product of dynamic interactions across institutional, pedagogical, and sociocultural systems. This framework provides actionable insights for policymakers, teacher educators, and school leaders to reinforce PAI’s moral mission, particularly in urban, media-saturated contexts, thus contributing to the broader discourse on character education in pluralistic societies.